Stannyl porphyrins, ferrocenyl porphyrins and nonplanar porphyrins : synthesis and photophysical properties - Bakar, Muntaz Abu (Trinity College (Dublin, Ireland). School of Chemistry, 2012)
The aim of this work was to synthesis the tin porphyrins, ferrocene porphyrins and nonplanar multiporphyrins arrays. The next step was to investigate their photophysical properties.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin.